Islamic Philanthropy Fiqh in Modern Context - Nanang Naisabur; Haris Maiza Putra; Chikal Anugrah Putra Naisabur; Diana Farid; Hisam Ahyani (Al-Muamalat: Jurnal Ekonomi Syariah, 2023)
This study aims to determine Islamic philanthropy in a modern context. Islamic philanthropy is taken from the religious doctrine of the Qur'an and hadith as a human and religious commitment so that Islamic charity appears as zakat, infaq, alms, and endowments. This type of research is qualitative with a literature study method. Data collection techniques in literature study are through books, articles, journals, and research reports related to the problem being researched. The results of the study found that in Indonesia, practices in zakat, waqf, infaq, and sadaqah (Ziswaf) are seen as economic symbols of justice and democracy, being able to place economic resources in their proper place. In conclusion, Islamic philanthropy in the modern context is a stylish way of managing one's social generosity in the context of carrying out muamalah activities among fellow human beings.